Interpolation of Basic Subjects in Colon Classification - Gupta, A. K. (Journal of Information and Knowledge, 1968)
Defines the necessary technical terms. Points out the need for provision for the Interpolation in the schedule of (BS) in a scheme for classification. Describes the various devices used by CC for such interpolation - Greek Letters, Sector Device, Emptying Digit, and Empty and Emptying Digits-at different times. Points out the resulting problems in the coordinate and subordinate status of (BS) with, particular reference to the Canonical (BS) of the (MS) "M Useful Arts" and the (MS) "N Fine Arts". Shows, with the help of the Mimamsa principle of "Burnt-Chariot Lost-Horse", that these problems are apparent but not real when examined at a deeper level. Explains the use of the digit-pair "-Z" (hyphen Z) for interpolating a Partial Comprehension of the Canonical (BS) between a (MS) and its first Canonical Division, and discusses the possible alternatives to this device.